The Roma and their struggle for identity in contemporary Europe - Baar, Huub van, 1970-; Kóczé, Angéla, 1970- (Romani studies (Berghahn Books), 2020)
"Thirty years after the collapse of Communism, and at a time of radically diverse kinds of identity politics, including anti-migrant, anti-Roma, anti-Muslim and anti-establishment movements, this book analyses how Roma identity is expressed in contemporary Europe. From backgrounds ranging from political theory, postcolonial, cultural and gender studies to art history, feminist critique and anthropology, the contributors reflect on the extent to which a politics of identity regarding historically disadvantaged, racialized minorities such as the Roma can still be legitimately articulated. In part, the contributors argue, the answer lies in a movement beyond classic identity politics and any opposition between essentialism and constructivism."--